Perceptions of Auditors in Malaysia on the Important Items of Internet Financial Reporting - Azli, Mohd Noor (Journal of Education and Vocational Research, 2013)
This study investigates the perceptions of auditors regarding the important items in the disclosure of content and presentation dimension that can be used to describe the level of internet financial reporting (IFR). Questionnaires were distributed to 100 auditors. A total of 40 questionnaires were completed and returned, giving a response rate of 40 percent. From the survey, it was found that the five most important items in the content dimension are income statement of current year, income statement of past years, cash flow statement of current year, notes to financial statements of current year and balance sheet of current year. Meanwhile, in the presentation dimension, five most items important to disclosure are loading time of the website below 10 seconds, annual report in PDF format, hyperlinks inside the annual report, ability to download reports and hyperlinks to financial analysts. Finally, the limitation of this study and future research will also be discussed.